2020
DOI: 10.1371/journal.pone.0240808
|View full text |Cite
|
Sign up to set email alerts
|

Do we visually estimate intra-operative blood loss better with white or green sponges and is the deviation from the real blood loss clinically acceptable? Results from a simulated scenario study

Abstract: Background The intraoperative blood loss is estimated daily in the operating room and is mainly done by visual techniques. Due to local standards, the surgical sponge colours can vary (e.g. white in US, green in Germany). The influence of sponge colour on accuracy of estimation has not been in the focus of research yet. Material and methods A blood loss simulation study containing four “bleeding” scenarios each per sponge colour were created by using expired whole blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…One interesting finding of our study was that there was no significant difference in estimated blood loss between the 2 cohorts (TXA vs no TXA). Although this finding was unexpected given the known reduction in blood loss after TXA administration, studies have shown that accurately estimating blood loss is a difficult task and depends on various factors, including color and types of sponges used intraoperatively 35–37 . Furthermore, there was no significant difference in operative time between the 2 cohorts.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One interesting finding of our study was that there was no significant difference in estimated blood loss between the 2 cohorts (TXA vs no TXA). Although this finding was unexpected given the known reduction in blood loss after TXA administration, studies have shown that accurately estimating blood loss is a difficult task and depends on various factors, including color and types of sponges used intraoperatively 35–37 . Furthermore, there was no significant difference in operative time between the 2 cohorts.…”
Section: Discussionmentioning
confidence: 87%
“…Although this finding was unexpected given the known reduction in blood loss after TXA administration, studies have shown that accurately estimating blood loss is a difficult task and depends on various factors, including color and types of sponges used intraoperatively. [35][36][37] Furthermore, there was no significant difference in operative time between the 2 cohorts. Our group anticipated that operative time may be decreased with the use of TXA and its role in reducing time to hemostasis; however, that was not the case.…”
Section: Discussionmentioning
confidence: 96%
“… 13 Visual estimation of blood loss is particularly inaccurate. 14 Having an experienced anesthesia team is an essential component to successful fluid and volume management. The triggers for transfusion of blood products include a hemoglobin less than 7/0 g/dL, abnormal coagulation parameters, obvious ongoing blood loss and abnormal vital signs but often the decision to transfuse may be subjective and influenced by experience.…”
Section: Discussionmentioning
confidence: 99%
“…There is no difference in the error of estimation between different types of healthcare professionals or level of experience; however, the fabric colour of swabs can have a significant influence on blood loss estimation: white swabs show a smaller value of deviation than green swabs. 19,20 Simulation training and the use of pictograms has been shown to improve visual estimation of blood loss, but this is not retained over time. 19,21 Direct or volumetric quantification of blood loss involves collecting and measuring blood loss in drapes and containers.…”
Section: Methods Of Estimating or Measuring Blood Loss During Obstetr...mentioning
confidence: 99%
“…Larger volume losses can be underestimated, increasing the risk of morbidity and mortality associated with significant PPH. There is no difference in the error of estimation between different types of healthcare professionals or level of experience; however, the fabric colour of swabs can have a significant influence on blood loss estimation: white swabs show a smaller value of deviation than green swabs 19,20 . Simulation training and the use of pictograms has been shown to improve visual estimation of blood loss, but this is not retained over time 19,21 …”
Section: Review Of Literaturementioning
confidence: 99%